ANALYSIS OF VOLATILITY, ASYMMETRY EFFECT AND LONG-TERM MEMORY ON FOREIGN EXCHANGE RATE USING THE GARCH ASYMMETRY MODEL - Nurrizky Budi Novindra, Farhan
Investment is one of the fields of passive income generation that is profitable. Investments can make someone rich, can also make an emergency fund, and retirement funds in old age. Two important factors influence an investment, namely returns and risks. One type of investment that can be used is an investment at a foreign exchange rate. Foreign exchange is the currency of other countries. One of knowledge field in physics to analyze stocks is Econophysics. Econophysics is a field of physics that applies concepts, methods, equations, and functions developed by a physicist in applying applications to economics. In making decisions in the world, a good analysis of volatility is needed. Volatility is the changes and fluctuations that occur in the stock price index. Long-term memory is a long-term correlation relationship found in time-series data. In this discussion, a time series of data modelling from the econophysics method can be used to analyze volatility, asymmetric effects, leverage effects, and long-term memory phenomena in time series data. The method used in this research are literature study, data collection in the form of daily foreign exchange rates, then modelling is done with a certain method. The models used to analyze stock prices are the ARIMA Model, the ARCH Model, the GARCH Model, the GJR-GARCH Model, and the EGARCH Model. From the results of the modelling obtained a result in the form of only CAD/IDR foreign exchange rates which have asymmetric effects and leverage effects. The USD/IDR foreign exchange rate has an asymmetric effect but has no leverage effect. The JPY/IDR foreign exchange rate has an asymmetrical effect, but it is not significant. The EUR/IDR and CNY/IDR foreign exchange rates have no asymmetric effects and leverage effects. The EGARCH model is better than the GARCH and GJR-GARCH methods. Foreign exchange rates that have volatility from the largest to the smallest are JPY/IDR, CAD/IDR, EUR/IDR, CNY/IDR, and USD/IDR. Investment strategies for risk takers investor can invest in JPY/IDR, CAD/IDR and EUR/IDR, while long-term investors can invest in CNY/IDR and USD/IDR. Investors must be careful when USD/IDR has a positive trend and when CAD/IDR has a negative trend. The five foreign exchange rates do not have long-term memory.